Pengaruh Risiko Pembiayaan Murabahah dan Istishna terhadap Kinerja Keuangan KB Bukopin Syariah - Murni Hayati; Rice Haryati; Sri Lismawati; Ethika Ethika (Neolectura, 2023)
The objective of this research to test the influence of Murabahah and Istishna Financing Risks on Financial Performance of KB Bukopin Sharia. Samples were Financial Statements of KB Bukopin Sharia listed BEI period 2018 until 2022. Variable in this research are Murabahah and Istishna Financing Risks as independen variable and Financial Performance as dependen variable. Measured of Murabahah Financing Risks variable used Non Performing Finance (NPF) of Murabahah. Measured of Istishna Financing Risks variable used Non Performing Finance (NPF) of Istishna. Whereas Measured of Value Financial Performance variable used Return on Assets (ROA). The regression model explores the relationship between Murabahah Financing Risk and Istishna Financing Risk and its contribution to the Financial Performance of KB Bukopin Sharia. The result reveal that Murabahah Financing Risk effected nagatively and insignificant to Return on Assets, Istishna Financing Risk effected nagatively and insignificant to Return on Assets, as well as Murabahah and Istishna Financing Risks effected nagatively and insignificant to Return on Assets of KB Bukopin Sharia.